Akupresur Sebagai Terapi Komplementer dalam Mengurangi Kecemasan pada Penderita Penyakit Tidak Menular: Narrative Review - Ni Made Laksmi Devi Jayanti. P; Made Suadnyani Pasek (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Non-communicable diseases (NCDs) are chronic health conditions that affect not only physical but also psychological well-being, including increased anxiety. Untreated anxiety can reduce quality of life and treatment adherence. Acupressure, as a form of complementary therapy, offers a safe and non-invasive approach to managing anxiety. This narrative review aims to evaluate the effectiveness of acupressure in reducing anxiety among patients with NCDs. Articles were searched using Google Scholar with keywords such as "acupressure", "anxiety", and various chronic diseases. Six studies with experimental and quasi-experimental designs were selected based on inclusion criteria, involving patients with cancer, chronic kidney disease, and osteoarthritis. The findings consistently demonstrated that acupressure reduced anxiety levels, whether performed by a therapist or self-administered, with commonly used points including ST36, LI4, and PC6. This review concludes that acupressure is an effective complementary therapy that can be incorporated into holistic care strategies for anxiety management in patients with NCDs.